The Impact Of Corporate Strategy On Investment Decision In Nigeria: Array - Efuntade, Olubunmi Omotayo; Olaniyan, Niyi Oladipo; Olusegun, Efuntade Alani (Acta Universitatis Danubius. Œconomica, 2020)
This study investigated the impact of corporate strategy on investment decision in Nigeria. The objective of the study was to examine how strategic planning and implementation impact the company’s expansion through investment decision in Nigeria. This study was predicated on the Penrose Theory of Firm Growth and Keynes’s Liquidity Preference Theory Primary data source was explored through the administration of questionnaires to respondents which was explored in presenting the facts of the situation from various investment companies in Lagos, Nigeria. The data collected from the respondents were analyzed using ex-post facto research design. Findings from the study revealed that corporate strategy has positive and significant impact on investment decision as this enhance company’s expansion depending on variable of interest. It was concluded that for organizations in Nigeria to remain competitive in business, it has to implement a thorough strategic plan on any investment decision in other to achieve their set goals. In fact, the level of strategy implemented often determines the level of investment decision because of the when the end result is positive it will definite improve their return on investment This study recommends that organizations should adopt best practices in their investment activities in order to keep abreast with the dynamics of global economic climate. Individual investors should internalize the habit of improving on their strategic pattern and investment information so that they can make better decisions and also investors should reinforce the need for a strategic framework for problem solving under complexities and the relevance of strategic considerations in investment planning. Lastly, individual investors and corporate organizations should internalize a process that would serve as a veritable tool for qualitative and thorough appraisal that is tailored towards improving project and investment performance. This study investigated the impact of corporate strategy on investment decision in Nigeria. The objective of the study was to examine how strategic planning and implementation impact the company’s expansion through investment decision in Nigeria. This study was predicated on the Penrose Theory of Firm Growth and Keynes’s Liquidity Preference Theory Primary data source was explored through the administration of questionnaires to respondents which was explored in presenting the facts of the situation from various investment companies in Lagos, Nigeria. The data collected from the respondents were analyzed using ex-post facto research design. Findings from the study revealed that corporate strategy has positive and significant impact on investment decision as this enhance company’s expansion depending on variable of interest. It was concluded that for organizations in Nigeria to remain competitive in business, it has to implement a thorough strategic plan on any investment decision in other to achieve their set goals. In fact, the level of strategy implemented often determines the level of investment decision because of the when the end result is positive it will definite improve their return on investment This study recommends that organizations should adopt best practices in their investment activities in order to keep abreast with the dynamics of global economic climate. Individual investors should internalize the habit of improving on their strategic pattern and investment information so that they can make better decisions and also investors should reinforce the need for a strategic framework for problem solving under complexities and the relevance of strategic considerations in investment planning. Lastly, individual investors and corporate organizations should internalize a process that would serve as a veritable tool for qualitative and thorough appraisal that is tailored towards improving project and investment performance.